The Effect of Local Taxes, Capital Expenditure, and GRDP on Regency/City Revenue in East Java Province - Dewi Anjar Khasanah; Ruth Eviana Hutabarat (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2026)
The research was motivated by the discrepancy between local revenue, capital expenditure, taxes, and economic growth, as well as by significant regional differences. Involving 38 districts/cities in East Java, the study aimed to analyze the effects of taxes, capital expenditure, and GRDP on local revenue. This study explains how all three factors simultaneously influence PAD. However, when tested to define the variables individually, GRDP cannot explain the increase or decrease in PAD. This phenomenon occurs because the economic structure of East Java does not automatically expand local tax revenue, indicating that fiscal decentralization has not fully benefited from all macro activities that are more concentrated in the authority of the central government.